2006
DOI: 10.1128/jb.188.6.2048-2055.2006
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Staphylococcus aureus ATP-Binding Cassette-ATPase FhuC for Iron-Restricted Growth and Evidence that It Functions with More than One Iron Transporter

Abstract: In Staphylococcus aureus, fhuCBG encodes an ATP-binding cassette (ABC) transporter that is required for the transport of iron(III)-hydroxamates; mutation of either fhuB or fhuG eliminates transport. In this paper, we describe construction and characterization of an S. aureus fhuCBG deletion strain. The ⌬fhuCBG::ermC mutation not only resulted in a strain that was incapable of growth on iron(III)-hydroxamates as a sole source of iron but also resulted in a strain which had a profound growth defect in iron-restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 50 publications
6
74
0
Order By: Relevance
“…Where siderophore production continues in the absence of transport, the growth medium represents a more chelated environment to the bacteria. To begin to assess this for S. aureus, we observed that when strains were grown in unchelated TMS broth (i.e., no exogenous chelator added), growth defects were noted for mutants lacking both staphyloferrin transporters (sir hts) or the ATPase required to energize both transporters (fhuC) (3,62). This growth defect was not apparent for a mutant unable to produce staphyloferrins (sbn sfa) (Fig.…”
Section: Fig 1 Growth Of S Aureusmentioning
confidence: 99%
“…Where siderophore production continues in the absence of transport, the growth medium represents a more chelated environment to the bacteria. To begin to assess this for S. aureus, we observed that when strains were grown in unchelated TMS broth (i.e., no exogenous chelator added), growth defects were noted for mutants lacking both staphyloferrin transporters (sir hts) or the ATPase required to energize both transporters (fhuC) (3,62). This growth defect was not apparent for a mutant unable to produce staphyloferrins (sbn sfa) (Fig.…”
Section: Fig 1 Growth Of S Aureusmentioning
confidence: 99%
“…Growth of the WT, sufD*, and sufD* suf ϩ strains was monitored in the presence of 2,2-dipyridyl (DIP), which is a cell-permeable divalent metal chelator with specificity for Fe (47). An fhuC::Tn mutant that is defective in Fe scavenging was included as an experimental control (48). The sufD* and fhuC::Tn strains displayed decreased growth compared to the WT when cultured in the presence of DIP, and the phenotype of the sufD* mutation could be genetically complemented (Fig.…”
Section: Iron-sulfur Cluster Synthesis In S Aureusmentioning
confidence: 99%
“…Construction of S. aureus isdE::K m -Allelic replacement, using methodologies described previously (38), was used to generate a non-polar insertion mutation in the chromosomal copy of isdE; the kanamycin cassette, from plasmid pDG782 (39), was inserted into a unique EcoRI site present within the isdE coding region. The Newman isdE mutant was named strain H834.…”
Section: Cloning and Protein Expression For Structure Determination-mentioning
confidence: 99%